Application of High-Resolution Flat Detector Computed Tomography in Stent Implantation for Intracranial Atherosclerotic Stenosis - Li, Tengfei; Wang, Yuting; Ma, Ji; Levitt, Michael; Mossa-Basha, Mahmud; Shi, Chengcheng; Ran, Yuncai; Ren, Jianzhuang; Han, Xinwei; Zhu, Chengcheng (Frontiers in Neuroscience, 2021)
Objective To evaluate the utility of high-resolution flat-detector computed tomography (HR-FDCT) compared with conventional flat-detector computed tomography (FDCT) for stent placement in symptomatic intracranial atherosclerotic stenosis (ICAS). Methods We retrospectively reviewed the clinical data of 116 patients with symptomatic ICAS who underwent stent implantation. Images were acquired using conventional FDCT [voxel size = 0.43 mm (isotropic)] and HR-FDCT [voxel size = 0.15 mm (isotropic)]. Immediately after stent deployment, dual-volume three-dimensional (3D) fusion images were obtained from 3D digital subtraction angiography (DSA) and HR-FDCT. The image quality for stent visualization was graded from 0 to 2 (0: not able to assess; 1: limited, but able to assess; 2: clear visualization), and the stent-expansion status (“full,” “under-expanded” or “poor apposition”) was recorded. Results A total of 116 patients with symptomatic ICAS were treated successfully using 116 stents (58 NeuroformTM EZ, 42 EnterpriseTM, and 16 ApolloTM). The mean pre-stent stenosis was 80.5 ± 6.4%, which improved to 20.8 ± 6.9% after stenting. Compared with FDCT, HR-FDCT improved visualization of the fine structures of the stent to improve the image quality that significantly (mean score: 1.63 ± 0.60 vs. 0.41 ± 0.59, P < 0.001). In 19 patients, stent under-expansion (n = 11) or poor apposition (n = 8) was identified by HR-FDCT but not by conventional FDCT. After balloon dilatation, stent malapposition was shown to have improved on HR-FDCT. None of the 19 patients with stent malapposition experienced short-term complications during hospitalization or had in-stent stenosis at 6-month follow-up. Conclusion High-resolution flat-detector computed tomography (HR-FDCT) improves visualization of the fine structures of intracranial stents deployed for symptomatic ICAS compared with that visualized using conventional FDCT. High-resolution flat-detector computed tomography improves assessment of stent deployment and could reduce the risk of complications.